KOMODIFIKASI KONTROVERSI ROCKY GERUNG DALAM PROGRAM KUPAS TUNTAS CNN INDONESIA - Adiputro, Budi; Sunarwan, Wahyudi (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2020)
Abstract The study is intended to analyze how talkshow with resource person and controversy as in Kupas Tuntas Program aired by CNN Indonesia is presented and commodified in such a way that the media institution could earn benefit as proven by the representation of ratings and audience responses. In the context of communication politics economy, the qualitative study here applies critical paradigm that uses Mosco’s arguments on the commodification of media content, audiences and labor. Television has built empirical realism construction into scene reality. As a result, contemporary community identity of both modern and post modern one has been bridged by media imagery which provides model and ideal notion that could serve as modeling of personal identity. Public is contented by controversy which is always questionable and debatable but never meet the audience’s satisfaction. Media then commodifies the controversy to get business profit in the context of media politics economy. The presence of Rocky Gerung in Kupas Tuntas Program aired by CNN Indonesia has evidently helped increase awareness and rating level to the program. Controversy and debate arising from the talkshow are also duplicated by various platforms of social media. Therefore, relationship of Rocky Gerung and media industry particularly television is deemed a mutual relationship. Keywords: Commodification, television, controversy, audiences, media content.